2022
DOI: 10.1177/11782218221096154
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Cannabis Use across Adolescence and Early Adulthood With Health and Psychosocial Adjustment in Early Adulthood and Midadulthood in Men

Abstract: Background: Associations between men’s prior cannabis use and their physical and psychosocial adjustment were examined using prospective data across adolescence (ages 13-20 years), early adulthood (ages 20-30 years), and midadulthood (ages 30-38 years). The theoretical framework was based in developmental-contextual and lifespan approaches. Method: Models were tested using men in the Oregon Youth Study who had been studied since ages 9 to 10 years and who, in childhood, lived in neighborhoods with higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Thus, also addressing adolescent boys' depressive symptoms may provide better leverage on their conduct problems and on later substance use via this route, as well as preventing other threats to adult health and adjustment associated with early depressive symptoms. 37 In a recent study with the OYS men of long-term risks of adolescent substance use, 38 it was found that cannabis use across adolescence and early adulthood was associated comprehensively with more detrimental psychosocial adjustment in early adulthood and midadulthood, respectively, in models that controlled for a number of early risk factors, including prior levels of the outcome variable where appropriate. Along with the findings of the present study, this indicates a high priority for public health should involve early prevention and treatment-at least for at-risk boys-that focuses on adolescents' conduct problems and substance use, including cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, also addressing adolescent boys' depressive symptoms may provide better leverage on their conduct problems and on later substance use via this route, as well as preventing other threats to adult health and adjustment associated with early depressive symptoms. 37 In a recent study with the OYS men of long-term risks of adolescent substance use, 38 it was found that cannabis use across adolescence and early adulthood was associated comprehensively with more detrimental psychosocial adjustment in early adulthood and midadulthood, respectively, in models that controlled for a number of early risk factors, including prior levels of the outcome variable where appropriate. Along with the findings of the present study, this indicates a high priority for public health should involve early prevention and treatment-at least for at-risk boys-that focuses on adolescents' conduct problems and substance use, including cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis use has been linked in cross-sectional and longitudinal studies to a range of academic outcomes including lower probability of high school graduation (Lorenzetti et al, 2020;Lynskey & Hall, 2000). Finally, adolescent cannabis use is associated with a range of factors commonly described as social determinants of health as well as individual, family, and peer progenitors of those conditional states (Capaldi et al, 2022;Hyshka, 2013).…”
Section: Discussionmentioning
confidence: 99%